Computing BER and outage probability for a cooperative relay network - Poh, Louis Chuang Hui (Nanyang Technological University, 2020)
In a cooperative relay network, it consists of 3 nodes, namely, a transmitter, a receiver and a relay node. In such a relay network system, to achieve cooperative diversity, cooperative relay protocol such as amplify-and-forward (AF), decode-and-forward (DF) and selective relay (SR) is then employed for a relay transmission. However, in order to determine the performance for such a system, Bit Error Rate (BER) and outage probability are fundamentally used as its prime performance metrics. This report will focus on simulating the computation of its BER and outage probability rate with various -ary modulation schemes such as BPSK over an AWGN channel and QPSK over an RF channel. With the increase in -ary phase shifting key, results have shown a significant reduction in BER user performance, especially in an 8 PSK modulation scheme. Apart from an AWGN channel and RF channel, this report also analyzes the AF cooperative relay network protocol that can achieve significantly lower BER as compared to an AWGN channel or RF channel.